Voting and Popularity - Gebhard Kirchgässner (Center for Economic Studies and ifo Institute (CESifo), 2016)
For about 45 years, vote and popularity functions have been estimated for many countries indicating that voting intentions as well as actual votes are influenced by economic development. The economy is, of course, not the only and probably not always the most important factor, but there is no doubt anymore that it is an important factor. The most relevant variables are still unemployment, and/or real growth, and inflation. The estimated coefficients vary considerably between countries and time periods. In papers, retrospective sociotropic voting dominates. However, the evidence is not so univocal; it rather tells that voting has egotropic as well as sociotropic aspects, and it is prospective as well as retrospective. It is still open what roles self-interest and altruism play in voting.
Keywords: H39; 330; vote and popularity function; egotropic and sociotropic voting; retrospective and prospective voting; rational voters' behavior